Yu-Gi-Oh GX. Vol. 4, The semifinals begin! - Kageyama, Naoyuki (Shonen Jump manga., 2010)
During the semifinal round of the Duel Academy tournament, Jaden and Bastion compete, while Chazz takes on David Rabb, with the winners advancing to battle one another.